PERANAN SEKOLAH TIONG HOA HWE KOAN DAN HOLLANDSCH CHINEESCH SCHOOL TERHADAP ETNIS TIONGHOA - Ratna Danyati; Samuel Budiman (Cakrawala - Jurnal Humaniora, 2012)
The problem to be discussed in this study on the background, differences, and the role of theestablishment of Chinese schools and Hollandsch Hwekoan Chineesch School. Historical researchmethods used to obtain an explanation and the corresponding analytical results. The research ismotivated in the reign of the Dutch East Indies are still very small number of schools, existingschools are schools formed by using the language of the Netherlands Dutch. Chinese leaders tocreate schools that can reach out to ethnic Chinese by using the language of Mandarin. To achievethis will be established a bevy of ethnic Chinese named Tiong Hoa Hwe Koan. At that time theDutch East Indies government worried about losing control of the Chinese people. Therefore theDutch East Indies government established a school named Hollandsch Chineesch School. Theschool is successfully competing with schools Tiong Hoa Hwe Koan. The results of this studyexplains that the role of the two schools both schools Tiong Hoa Hwe Koan and HollandschChineesch School is very large, especially in introducing literacy to children Chinese. Tiong HoaHwe Koan school itself plays a role in the country include the teaching of Chinese communistswhile Hollandsch Chineesch School brought changes to the conviction of people who originallyConfucian religion changed to Christianity or Catholicism.Keywords: Netherlands Dutch, Tiong Hoa Hwe Koan, Hollandsch Chineesch School